2004
DOI: 10.1007/s00391-004-0229-y
|View full text |Cite
|
Sign up to set email alerts
|

Activity of antioxidant enzymes and concentration of lipid peroxidation products in selected tissues of mice of different ages, both healthy and melanoma-bearing

Abstract: The activity of antioxidant enzymes and the concentration of the lipid peroxidation product malondialdehyde (MDA) as indicator of oxidative damage were determined in selected tissues of healthy mice and transplanted B16 melanoma-bearing mice with increasing age. A total of 60 male mice were divided into 6 groups. Groups 1, 2 and 3 consisted of tumor-free, healthy mice aged 1, 9 and 16 months, respectively (average life span: 2 years). Groups 4, 5 and 6 consisted of mice of the same age as the healthy mice, but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 19 publications
2
23
1
Order By: Relevance
“…There were no statistical differences in the total enzyme activity in the group of older and younger females which may suggest no dependence on age in livers of these animals, which is also confirmed by other authors (Tian et al 1998, Sverko et al 2004). There are, however, others who observed increased SOD activity during ageing in mice (Wozniak et al 2004).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…There were no statistical differences in the total enzyme activity in the group of older and younger females which may suggest no dependence on age in livers of these animals, which is also confirmed by other authors (Tian et al 1998, Sverko et al 2004). There are, however, others who observed increased SOD activity during ageing in mice (Wozniak et al 2004).…”
Section: Discussionmentioning
confidence: 91%
“…Meng et al (2007) found a significant decrease in SOD activity in the kidney, brain, and heart during aging in rats as well as a higher activity of CuZn-SOD than Mn-SOD in older compared to younger animals. Wozniak et al (2004) observed doi: 10.17221/8406-CJAS an increase in enzymatic activity in older animals, but also a decrease in erythrocytes with age. No effect of age on SOD activity was noticed in the mouse brain (Hamilton et al 2001), in the liver of mice (Sverko et al 2004) as well as in the rat muscles (Chen et al 2008).…”
Section: Introductionmentioning
confidence: 93%
“…SOD, CAT and GPx are the main antioxidant enzymes of the biological system (Wozniak et al, 2004;Slavic et al, 2006;Lestaevel et al, 2009). CAT can convert hydrogen peroxide to molecular oxygen and water.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, HO-1 has been reported to increase in brain and liver tissues with aging (81,82), whereas SOD and CAT activities were increased in the brain, and CAT and GPx were elevated in the liver of aged mice (83). Moreover, SOD, CAT, and GPx activities increase in different regions of the aged C57BL/6N brain (84).…”
Section: Discussionmentioning
confidence: 95%
“…Phase II enzymes play an important role during aging, with data from various laboratories showing age-related changes in phase II enzyme expression, with some specificity with respect to tissue type, organelle, animal strain, and sex (81)(82)(83)(84)(85)(86)(87). For instance, HO-1 has been reported to increase in brain and liver tissues with aging (81,82), whereas SOD and CAT activities were increased in the brain, and CAT and GPx were elevated in the liver of aged mice (83).…”
Section: Discussionmentioning
confidence: 99%